1924
DOI: 10.1085/jgp.7.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Studies in the Physical Chemistry of the Proteins

Abstract: It has not often been possible to consider the relation between the composition of proteins and their behavior. This has been due, in part, to the complexity of this class of substances; a complexity often as bewildering as the organizations and symmetries of the biological systems which proteins constitute, and always more intricate than the stereochemistry of the simpler organic compounds of which proteins are, in turn, composed. The large molecular weights of the proteins, and the large number of amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1927
1927
1955
1955

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The results on -aminobutyric acid, together with the results on solutions in alcohol-water mixtures, are given in table 4. The results on glycine are essentially the same.…”
Section: E Amidesmentioning
confidence: 69%
See 2 more Smart Citations
“…The results on -aminobutyric acid, together with the results on solutions in alcohol-water mixtures, are given in table 4. The results on glycine are essentially the same.…”
Section: E Amidesmentioning
confidence: 69%
“…Similar data are available for the three benzbetaines and glycine betaine, which, as we have pointed out, probably exist wholly in the form of dipolar ions under all conditions. In figure 3 are shown the results of Edsall and Wyman (22) on solutions in ethanol-water and ethanol-benzene mixtures, and in figure 4 fairly constant and there is no considerable difference between the two sets of solvents. This is like the case of the two amino acids studied.…”
Section: E Amidesmentioning
confidence: 88%
See 1 more Smart Citation
“…A patent issued to Osborne and Cornelison (8) was based upon the extraction of zein from crude corn gluten by adding to a water suspension of this gluten "enough caustic soda or caustic potash to impart to the mixture a decided alkaline reaction with phenolphthalein." Cohn, Berggren, and Hendry (6) found that zein will not readily dissolve in aqueous ammonia, and that a pH of 10 or higher must be reached before solution occurs in alkali. Smith,Max,and Handler (9), during studies on the dispersion of proteins in formaldehyde, found that maximum dispersion of zein in alkali was obtained at a pH of approximately 12.6, and that the addition of formaldehyde shifted the point of maximum dispersion to a pH of approximately 10.7.…”
mentioning
confidence: 99%